Between Philosophy and Self-Reflection - Daujotytė-Pakerienė, Viktorija (Literatūra, 2020)
The article aims at highlighting the uniqueness of thinking and academic activity of Donatas Sauka, who for many years was a professor at the Department of Lithuanian Literature of Vilnius University. The article reveals his scholarly ambitions – broad interests, good knowledge of classic Western literature, and an attempt to keep the achievements of natural sciences on the horizon of humanities. However, he harboured artistic and poetic inclinations in his nature; he has translated a number of classical texts required for his research. The philological interests of the professor were permeated by self-reflection. Comparative literature science was his field of research – even though his other interests also competed for his attention, he analysed methodological issues, different scopes of national literatures and paradoxes of literary analysis. He also raised an essential question for comparison – from what and how are clusters of literary identity formed; how they are related to the mental history and language of a nation; how creative incentives are formed and how they operate.